2017
DOI: 10.1007/s11356-017-9956-7
|View full text |Cite
|
Sign up to set email alerts
|

Performance, emission, and combustion characteristics of twin-cylinder common rail diesel engine fuelled with butanol-diesel blends

Abstract: Nitrogen oxides and smoke are the substantial emissions for the diesel engines. Fuels comprising high-level oxygen content can have low smoke emission due to better oxidation of soot. The objective of the paper is to assess the potential to employ oxygenated fuel, i.e., n-butanol and its blends with the neat diesel from 0 to 30% by volume. The experimental and computational fluid dynamic (CFD) simulation is carried out to estimate the performance, combustion, and exhaust emission characteristics of n-butanol-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It was witnessed that with the addition of 1‐hexanol in RCCI mode using B20 as the primary fuel, the gradual improvement in the in‐cylinder pressure was observed up to 30% 1‐hexanol share. This is due to the occurrence of additional oxygen in 1‐hexanol, as well as the fact that it has sufficient time for better mixing, ensuing in improved mixture homogeneity and enhanced combustion 21,31 . Beyond 30% 1‐hexanol, the decline in peak pressure was noticed due to the reduction in the quantity of pilot fuel in the main injection as the alcohol concentration rises in the intake manifold, affecting the ignition quality during combustion 28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was witnessed that with the addition of 1‐hexanol in RCCI mode using B20 as the primary fuel, the gradual improvement in the in‐cylinder pressure was observed up to 30% 1‐hexanol share. This is due to the occurrence of additional oxygen in 1‐hexanol, as well as the fact that it has sufficient time for better mixing, ensuing in improved mixture homogeneity and enhanced combustion 21,31 . Beyond 30% 1‐hexanol, the decline in peak pressure was noticed due to the reduction in the quantity of pilot fuel in the main injection as the alcohol concentration rises in the intake manifold, affecting the ignition quality during combustion 28 .…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the occurrence of additional oxygen in 1-hexanol, as well as the fact that it has sufficient time for better mixing, ensuing in improved mixture homogeneity and enhanced combustion. 21,31 Beyond 30% 1-hexanol, the decline in peak pressure was noticed due to the reduction in the quantity of pilot fuel in the main injection as the alcohol concentration rises in the intake manifold, affecting the ignition quality during combustion. 28 In addition, an increased cooling effect due to the higher latent heat of vaporization of 1-hexanol resulted in a reducing-cylinder pressure and heat release rate (HRR).…”
Section: In-cylinder Pressurementioning
confidence: 99%
“…Errors and uncertainties may arise due to various parameters such as calibration, environmental conditions, observation, reading, equipment selection and test planning [27,49]. Uncertainty analysis measures the accuracy of the experiments performed [50]. In this thesis study, the uncertainty analysis was performed by taking into account the uncertainties of the devices used in the experiments in order to increase the accuracy of the results observed [51].…”
Section: Test Methodologymentioning
confidence: 99%
“…It was found that 20% of butanol blend resulted in decreased NO x and soot emissions without much penalty on the engine performance. Venkatesh et al studied the effect of butanol/diesel blends (0% to 30% of butanol volume) on a twin‐cylinder common rail direct injection (CRDI) diesel engine by the varying injection timing (9°, 12°, 15°, and 18° bTDC). It was reported that the BTE increased and, NO x , soot and CO emissions decreased with the increase of butanol fraction in the blend.…”
Section: Introductionmentioning
confidence: 99%